2017
DOI: 10.3390/su9122213
|View full text |Cite
|
Sign up to set email alerts
|

Delimiting Urban Growth Boundary through Combining Land Suitability Evaluation and Cellular Automata

Abstract: China's domestic urban planning only worked on researches of urban space control, the scope definition of urban development is not clear enough. The purpose of this study is to present a new urban growth boundary (UGB) delimitation method which combined land suitability evaluation (LSE) and cellular automata (CA). This method gave credence to LSE's advantage in sustainable land use, and CA's advantage in objective dynamic simulation. The ecological limitation areas were defined by LSE, which were regarded as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 32 publications
0
21
0
1
Order By: Relevance
“…The literature indicates that the delineation of UGBs can benefit from using urban growth models or land use change simulation models., including cellular automata (CA) and agent based model (ABM) [6,7,[9][10][11][12][13][14][15][16], such as SLEUTH [17], CLUE-s [18], and GEOMOD [19]. Some influential studies and plans have applied these models to help determine UGBs [6,7,[20][21][22].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature indicates that the delineation of UGBs can benefit from using urban growth models or land use change simulation models., including cellular automata (CA) and agent based model (ABM) [6,7,[9][10][11][12][13][14][15][16], such as SLEUTH [17], CLUE-s [18], and GEOMOD [19]. Some influential studies and plans have applied these models to help determine UGBs [6,7,[20][21][22].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some authors suggested making additional adjustments to the final UGBs or UDBs by integrating other policy considerations and by excluding spatial control areas (e.g., redline ecological areas, restrictive development areas, farmland protection areas; B. Zheng et al 2018; Q. Zheng et al 2017; Zhuang et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The development of an integrated modelling-measurement system for the near-real-time assessment of port activities on air pollution could strengthen port pollution management and improve the air quality in port cities [90]. The use of the urban growth boundary (UGB) delimitation method [91], the implementation of integrated territorial investments (ITI) [92], the improvement of the utilization efficiency of urban land [93], and the designing of urban blue space [94] could promote the sustainability of the ecological environment of port cities. Using material flow analysis (MFA) to analyze the urban metabolism (UM) was conducive to resource management and supported the sustainable environmental planning of port cities [95].…”
Section: Research Focusesmentioning
confidence: 99%